Shareholder bargaining power and the emergence of empty creditors - Stefano Colonnello; Matthias Efing; Francesca Zucchi (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2018)
Credit default swaps (CDSs) can create empty creditors who potentially force borrowers into inefficient bankruptcy but also reduce shareholders' incentives to default strategically. We show theoretically and empirically that the presence and the effects of empty creditors on firm outcomes depend on the distribution of bargaining power among claimholders. Firms are more likely to have empty creditors if these would face powerful shareholders in debt renegotiation. The empirical evidence confirms that more CDS insurance is written on firms with strong shareholders and that CDSs increase the bankruptcy risk of these same firms. The ensuing effect on firm value is negative.
urn:nbn:de:gbv:3:2-94060
Keywords: G32; G33; G34; 330; empty creditors; credit default swaps; bargaining power; real effects